REPRODUCTIVE PERFORMANCE DURING PARASITIC LOADS AND ITS CONTROL IN DOES - MAHTO, DINESH; SINGH, L B; SINHA, M P; SINGH, D K; DRON; JHA, D K (The Indian Journal of Animal Reproduction, 2023)
A total number of 18 does, which had kidded at least once and were found positive for common intestinalnematodes, were treated with Albendazole (Helmigard) @ 5mg/kg body weight orally along with a supportivetherapy of mineral mixture (Calvimin)@ 10 gm orally daily for 20 days. Six goats were kept as untreated control.The minimum interval from treatment to onset of estrus in does was recorded in Albendazole + Mineral mixturegroup (43 days) which was followed by Albendazole group (46 days) and control group (52days), the averagerequired number of services per conception in does were 1.33, 1.00 and 2.00, respectively. The pregnancy ratesin the three groups were 66.66, 83.33 and 33.33%, respectively in case of does. The Albendazole along withMineral mixture can be administered to the parasitized goats to improve their reproductive performances.
Keywords: Albendazole; Mineral; Nematodes; Estrus and Does